Healthy Snack for Diabet Patients with Cocoyams Tubers - Rosida , Dedin Finatsiyatull; Anggraeni, Fetty Tri (Nusantara Science and Technology Proceedings, 2020)
Diabetes Mellitus sufferers are estimated to have reached 9.1 million people. This data makes Indonesia ranked 5th in the world with the highest Diabetes Mellitus. Diabetes Mellitus is one of the main causes of non-communicable diseases or 2.1% of all deaths, including East Java province. The key to managing blood sugar levels is managing carbohydrate intake. This is because carbohydrates are responsible for raising blood sugar levels. Managing the number of carbohydrates is the main goal, although choosing slow-digesting carbohydrates with high fiber content. Apart from carbohydrates, diabetics also need to limit their intake of salt, saturated fats and avoid trans fats. People with diabetes need to include fiber and healthy fats in their daily diet. People with diabetes have a higher risk of developing hypertension, high cholesterol, and heart disease than the general population. It is very important to consider these risks when planning a diet. For that, we need snacks that are low in calories and have high levels of dietary fiber and low trans fat content. UPN Veteran Jawa Timur through the Community Innovation Service Program (BIMA) provides training to UD. Rinjani Cookies to produce various snacks made from cocoyam tubers (Kimpul) with high enough healthy nutrition. The snack products offered were cookies, brownies, kimpul layers cake, and kimpul banana cakes. This snack is healthy for people with Diabetes Mellitus because it is rich in fiber, low calory, and does not contain trans fats